Rational Design of Fluorophores Using MO Theory: Our Journey from BODIPYs to BOIMPYs - Patalag, Lukas J.; von Köller, Heinrich F.; Werz, Daniel B. (Organic Materials, 2024)
This short review demonstrates how MO-theoretical considerations can support the tailor-made design of new dye scaffolds, specifically the recently introduced BOIMPY class of fluorophores. Starting with historical and structural foundations, the influence of canonical streptocyanines on the electronic features of diarylmethenes and rhodamines is examined and the BODIPY scaffold is introduced as the primary structural inspiration for our work. The attachment of five-membered ring heterocycles at the meso position of the BODIPY core enables a relaxation into a co-planar and twofold chelating triarylmethene system. After introduction of two electron-withdrawing BF2 units, efficient rigidity is achieved since hindered rotation prevents non-radiative dissipation of energy via excited state relaxation. Hence, a lowered LUMO level allows the combination of a large red shift with high quantum efficiencies. The synthetic approach to BOIMPYs is straightforward and analogous to BODIPY syntheses starting from benzimidazole or tetrazole carbaldehydes. Cyclic voltammetric measurements prove that BOIMPYs are able to easily accept two electrons and might act as efficient photoredox catalysts.
Keywords: fluorophores; dyes; BODIPY; BOIMPY; MO considerations